ATRIAL FIBRILLATION COMBINED WITH ARTERIAL HYPERTENSION AND OBESITY PARADOX - L. D. Khidirova; D. A. Yakhontov; T. S. Kuropiy; S. A. Zenin (Евразийский Кардиологический Журнал, 2019)
Purpose. To study the peculiarities of the clinical course of atrial fibrillation in patients with arterial hypertension and obesity.Materials and methods. 127 patients were observed within the observational cohort studies. Of these, 64 patients with atrial fibrillation, arterial hypertension and obesity in the control group, while the experimental group consisted of 63 patients with atrial fibrillation, arterial hypertension and normal BMI (24.1±2.2) kg/m2. During our work we assessed clinical, anthropometric and laboratory indicators, as well as the results of instrumental examination: ElectroCG; Daily monitoring of ECG, EchoCG. Comparison of binary and categorical indicators was carried out upon an accurate bilateral F test. Statistical hypothesis testing was carried out at critical significance value p=0.05, i.e. the difference was considered statistically significant if p<0.05.Results. Body mass index (BMI) in patients with atrial fibrillation, hypertension and obesity amounted to 35.2±4.6 kg/m2. The average age in all clinical groups was 60.5±9.2 years old, and patients with obesity were significantly younger (p<0.05) - 53.3±6.1 years old than patients with normal BMI - who were 59.8±7.4 years old. Patients with hypertension, atrial fibrillation and obesity often had a persistent form of AF 71%. General assessment of the lipid profile indicated that only patients with obesity and hypothyroidism showed a significantly high level of triglycerides. (p<0.001). There was an increase in NT-proBNP (p=0.001) and galectin-3 (p=0.005). There was a consistent increase of the end-diastolic dimension of the left ventricle in the left atrium; thickening of the left ventricular posterior and the interventricular septum in compared groups proved equivocal, while the LVMMI (p<0.05) was significantly lower in patients with obesity than in the experimental group.Conclusion. The presence of obesity in patients with atrial fibrillation and arterial hypertension adversely affects certain biochemical and ultrasound parameters, however, many of the criteria characterizing cardiovascular risk and prognosis did not reveal significant differences, which requires further in-depth study of this problem and identification of a possible “obesity paradox” in the group of patients with atrial fibrillation, arterial hypertension and obesity.